prove newton's 2nd law of motion
Answers
Answered by
6
Average V=(v+u)/2
Also V=S/t
:.v=(v+u)/2=s/t
(V+u)/2=s/t
Now from 1st equation we know that.
V=u+at
:. Putting value
(U+at+u)/2=s/t
(2u+at)/2=s/t
U+at/2=s/t
(U+at/2)t=s
UT+at²/2=s
Newton's second law of motion
Hence, proved.
(ÆÑẞWĒR)
#Mærk ãß thē Bråìñlìêßt
Rëgārdß
Tèàm Káñçhâ
Also V=S/t
:.v=(v+u)/2=s/t
(V+u)/2=s/t
Now from 1st equation we know that.
V=u+at
:. Putting value
(U+at+u)/2=s/t
(2u+at)/2=s/t
U+at/2=s/t
(U+at/2)t=s
UT+at²/2=s
Newton's second law of motion
Hence, proved.
(ÆÑẞWĒR)
#Mærk ãß thē Bråìñlìêßt
Rëgārdß
Tèàm Káñçhâ
Nikhilsoni610:
good job but its not newton 2nd law of motion
Answered by
5
Explanation:
ùr ãñswer høpe it helps you ✌️
please mark me as brainliest ✌️
Attachments:
![](https://hi-static.z-dn.net/files/d95/7f19a9c210dea53206a19140d475ed89.jpg)
Similar questions